(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Customer satisfactionis one of the formidable challenges in marketing of services in bankingindustry in our country. The thrust on customer service has increased afterliberalisation of Indian economy. Customer satisfaction is an urgent need ofthe hour.